2018
DOI: 10.2166/wp.2018.073
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the distributional impacts of water subsidy policy in Chile: a historical analysis from 1998–2015

Abstract: The distributional incidence of the Chilean water subsidy scheme is revisited by analyzing its evolution from 1998 to 2015. This is one of the only means-tested water subsidies in a developing country and is frequently used as an example in policy discussions and recommendations. Many changes have been introduced in the program since its inception and at least three different targeting instruments have been used to identify needy households in the last 20 years. We find that the incidence of the subsidy is pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…In these neighbourhoods, access to network infrastructure services has become increasingly hard, not because of lack of physical infrastructure, but because of the cost of privatised services. Water bills, for instance, have had to be subsidised by the state: by 2015, more than 800,000 households received a water subsidy in Chile (Contreras et al, 2018). As is evident in the interviews, the Internet is increasingly being seen as a basic service, similar to water, sanitation, electricity, and waste collection.…”
Section: Two Neighbourhoods In Santiagomentioning
confidence: 99%
“…In these neighbourhoods, access to network infrastructure services has become increasingly hard, not because of lack of physical infrastructure, but because of the cost of privatised services. Water bills, for instance, have had to be subsidised by the state: by 2015, more than 800,000 households received a water subsidy in Chile (Contreras et al, 2018). As is evident in the interviews, the Internet is increasingly being seen as a basic service, similar to water, sanitation, electricity, and waste collection.…”
Section: Two Neighbourhoods In Santiagomentioning
confidence: 99%
“…Indeed, direct subsidies offer an interesting contrast to indirect subsidies or crosssubsidization. In this way, the Chilean water subsidy model promotes better targeting of the benefit towards poor customers than other schemes found in developing countries [29].…”
Section: Chilementioning
confidence: 99%
“…With respect to the Latin American region, some works have looked at the incidence of the federal subsidies to residential public services. This body of research has found that although subsidies can be a tool to protect the poor, a large share have been absorbed by upper classes and non-residential consumers in Argentina [5], and that depending on the targeting strategy, the effectiveness of the subsidy at reaching poor households might be moderate as described by Contreras, Gomez-Lobo, and Palma [6] in Chile and Colombia [7], or even decrease the proportion of poor households receiving benefits as mentioned by Barde and Lehmann [8] for the case of Peru. For the special case of Mexico City, Morales-Novelo et al [9] have shown that residential water subsidies have a regressive structure benefiting wealthier households more heavily than poorer families in the city.…”
Section: Literature Reviewmentioning
confidence: 99%